Analysis of Competencies Among Students in Adopting Education 4.0 at Higher Learning Institution in Johor - SHAFI, MUHAMMAD AMMAR (Research in Management of Technology and Business, 2023)
The development of technologies such as education 4.0 over time has affected the education sector This study has been conducted because the implementation of education 4.0 is still at starting point in Malaysia. This study attempts to determine the level of competencies among students in adopting education 4.0, to determine the level of performance in adopting education 4.0 among students and to determine the relationship between competencies in adopting education 4.0 and performance in adopting education 4.0. The study was focusing on students in University Tun Hussein Onn Malaysia (UTHM) and University Teknologi Malaysia (UTM). The study used a quantitative approach, and information has been gathered by giving out questionnaires to participants. Utilizing the Statistical Package for Social Science, the data has been examined (SPSS) and Microsoft Excel. The data from 379 valid respondents were gathered for the study using an online survey form. The results show that the level of competencies influence performance in adopting education 4.0 among students in UTHM and UTM. This research found that when competencies increase, then the performance in adopting education 4.0 also increase.